Physical Chemical and Sensory Effect of Kanom Gleeb-Lum-Duan (Thai Shortbread Cookies) Substituted Wheat Flour with Khao Bou Yod Mung Rice flour - Tas-eaim, Vuschapuk; Suteebut, Nomjit; Naknean, Phisut; Tubbiyam, Prassanee (Journal of Food Technology, Siam University, 2026)
The objectives of this research were to study the physical and chemical properties of Khao Bou Yod Mung rice flour and study the suitability substitution level of Khao Bou Yod Mung rice flour for wheat flour in Gleeb-Lum-Duan. Analysis of Khao Bou Yod Mung rice flour revealed L*, a*, and b* values of 70.64, 7.43, and 12.47 respectively, with a water activity of 0.64. Its chemical composition Khao Bou Yod Mung rice flour showed higher levels of fat, ash, carbohydrates, and dietary fiber, while its protein and moisture contents were lower than those of wheat flour. Energy 372.74 kcal. Antioxidant activity was 23.25% and total phenolic content was 0.38 mg/g. The results suitability substitution level of Khao Bou Yod Mung rice flour for wheat flour in Gleeb-Lum-Duan with 5 different levels. Panelists accepted Gleeb-Lum-Duan with 40% Bou Yod rice flour substitution showed no significant difference from the control. Increasing the replacement of Khao Bou Yod Mung rice flour resulted in decreased L* and b* values but increased a* values, reflecting the inherent color characteristics of the rice flour, with water activity of 0.15, with a hardness of 161.88. Its chemical composition per 100 g was 24.79 g fat, 5.94 g protein, 1.04 g moisture, 0.85 g ash, 67.38 g carbohydrates, and 2.08 g dietary fiber, energy 516.39 kcal. Antioxidant activity was 18.37% and total phenolic content was 0.16 mg/g. This product serves as a healthy alternative for health-conscious consumers. It possesses the potential for industrial-scale production and further development into a local specialty or an OTOP brand.